Preparation of highly efficient thermoelectric Bi-doped Mg2Si0.55-xSn0.4Gex (x = 0 and 0.05) materials with a scalable mechanical alloying method - Symeou, Elli; Karyou, M.; Delimitis, Andreas; Constantinou, Marios; Constantinides, Georgios; Nicolaou, Ch.; Giapintzakis, Ioannis; Kyratsi, Th (My University, 2022)
Mg2Si-type compounds are highly promising materials for use in thermoelectric devices for waste heat energy harvesting. These compounds have great potential because they exhibit high thermoelectric performance, but the scalability of their synthesis is a major issue for applications. In this study, Bi-doped Mg2Si0.55-xSn0.4Gex (x = 0 and 0.05) materials were prepared by mechanical alloying combined with hot press sintering in order to increase the mass capabilities of their synthetic route compared with the typical solid state reaction. The optimum thermoelectric properties were achieved for the best Mg2Si0.57Sn0.4Bi0.03 and Mg2Si0.53Sn0.4Ge0.05Bi0.02 compositions by ball milling for 32 h and the maximum figure of merit (ZT) values were 1.07 and 1.2, respectively.
Keywords: Magnesium silicide; Mechanical properties; Solid state reaction synthesis; Thermoelectric properties; Mechanical alloying; Ball milling